RESEARCH STUDY ON IMPLEMENTATION BY THE EEU OF "OTHER INTERNAL MARKET PROTECTIVE MEASURES" AND THEIR ROLE IN THE REGULATION OF THE IMPORT OF GOODS - Khodzhadurdy Amandurdyev; Artur Orazaliev; Tat'yana Tolmacheva (Вестник Северо-Кавказского федерального университета)
The article covers distinctive features and peculiarities of the «other internal market protective measures», application of which stipulated in the EEU Agreement (Articles 48 and 50). The research revealed characteristics of tariff quotas as internal market protective measures, that separate them from the special protective, anti-dumping and countervailing measures; assessed the role of the "other internal market protective measures" in regulating import of certain types ofgoods into the EEUfrom a third party, with which a free trade agreement is concluded.